The Effect of Co-branding Strategy Elements on Consumer Attitude and Purchase Intention : A Study in Indonesia - Rafiati Kania; Kuntihapsari Sri Sukoyo; Nono Wibisono (Journal of Marketing Innovation (JMI), 2021)
According to brand alliance literature, the compatibility of brand characteristics in co-branded products will raise consumer positive attitudes and purchase intention. Previous research has explored the co-branding strategy between the same sector or complement product character from different sector. However, little research has been conducted on the exploration of the co-branding strategy in a different sector with less complement character. This study seeks to construct the value of co-branding strategy of influencing female consumer attitude as well as its purchase intention. It relates to the less-known Indonesian cosmetics brand who invite well-known food brands to create blended characteristics of cosmetic products. Three co-branded products namely Mizzu Cosmetics x Khong Guan Biscuits, Dear Me Beauty x Yupi, Dear Me Beauty x Sasa, and Dear Me Beauty x Nissin as the objects of this research. A total of 358 questionnaires were distributed to female cosmetic consumers aged between 19-41. The proposed research model has been tested using PLS-SEM. The findings highlight prior attitudes toward host brands that have weak influence attitude toward co-branded products. However, the brand fit could mediate prior attitude toward host brand in influencing attitude toward co-branded product. By mediating the roles of brand fit, the attitude toward co-brand and post-attitude toward host brand show important value in the element of consumer attitude and purchase intention. A well-known and suitable co-branding partner is needed to give exposure to the co-branded product and provide a spill-over effect for the host brands. This study contributes to add spill-over effect phenomenon in brand alliance literature.